A model of sustainable development of scientific research health institutions, providing high-tech medical care - I. Yu. Bedoreva; L. S. Shalygina; O. A. Latukha (Бюллетень сибирской медицины)
The issue of sustainability is relevant for all types of businesses and organizations. Long-term development has always been and remains one of the most difficult tasks faced by organizations. The implementation the provisions of international standards ISO series 9000 has proven to be effective. The ISO standards are concentrated on the global experience for sustainable success of organizations. The standards incorporated all the rational that has been accumulated in this field of knowledge and practice. These standards not only eliminate technical barriers in collaboration and have established standardized approaches, but also serve as a valuable source of international experience and ready management solutions. They became a practical guide for the creation of management systems for sustainable development in organizations of different spheres of activity.Problem and purpose. The article presents the author’s approach to the problem of sustainable development health of the organization. The purpose of this article is to examine the approaches to management for sustainable success of organizations and to describe a model of sustainable development applied in research healthcare institutions providing high-tech medical care.Methodology. The study used general scientific methods of empirical and theoretical knowledge, general logical methods and techniques and methods of system analysis, comparison, analogy, generalization, the materials research for the development of medical organizations.The main results of our work are to first develop the technique of complex estimation of activity of the scientific-research institutions of health and deploy key elements of the management system that allows the level of maturity of the management system of the institution to be set in order to identify its strengths and weaknesses, and to identify areas for improvements and innovation, and to set priorities for determining the sequence of action when implementing process improvement. Factors required for use in the management of the organization are critical to sustainable success.Conclusion. The authors observed that the implementation of the quality management system, continuous its maintenance for 15 years, and its transformation in the management system of sustainable development has improved all key performance indicators of the Novosibirsk NRITO. Positive results are confirmed by the results of self-evaluation management system for key elements, i.e. the determination of the level of maturity and tangible improvement at this level during the period of implementation of the system of sustainable development from the second to level 4 (advanced control system).